#### Answer

$-10-30i$

#### Work Step by Step

$\bf{\text{Solution Outline:}}$
To simplify the given expression, $
5i(-6+2i)
,$ use the Distributive Property. Then use $i^2=-1$.
$\bf{\text{Solution Details:}}$
Using the Distributive Property which is given by $a(b+c)=ab+ac,$ the expression above is equivalent to
\begin{array}{l}\require{cancel}
5i(-6)+5i(2i)
\\\\=
-30i+10i^2
.\end{array}
Since $i^2=-1,$ the expression above is equivalent to
\begin{array}{l}\require{cancel}
-30i+10(-1)
\\\\=
-30i-10
\\\\=
-10-30i
.\end{array}